2021
DOI: 10.1016/j.metop.2021.100108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of dyslipidemia among hypertensive patients in Lumame Primary Hospital, Amhara, Ethiopia: A cross-sectional study

Abstract: Background Serum lipid profile abnormalities are major predictors for coronary artery diseases. The relationship between demographic factors and dyslipidemia in Ethiopia is not completely explored. Thus, this study aimed to assess the prevalence and predictors of dyslipidemia among hypertensive patients in Lumame Primary Hospital. Methods A cross-sectional study was conducted from June to August 30, 2020, on the hypertensive patients in Lumame Primary Hospital. All adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 67 publications
9
5
2
Order By: Relevance
“…From the results of the present study, at least 50% of the study participants were at increased risk of cardiovascular events due to dyslipidaemia. A similar high prevalence of dyslipidaemia has been reported in other African countries among people living with DM and hypertension [38][39][40]. The lack of screening and management of dyslipidaemia in the present study highlights the gap in addressing the burden associated with dyslipidaemia in high-risk individuals with DM and hypertension in Malawi, hence contributing to the high burden associated with CVDs [34].…”
Section: Discussionsupporting
confidence: 78%
“…From the results of the present study, at least 50% of the study participants were at increased risk of cardiovascular events due to dyslipidaemia. A similar high prevalence of dyslipidaemia has been reported in other African countries among people living with DM and hypertension [38][39][40]. The lack of screening and management of dyslipidaemia in the present study highlights the gap in addressing the burden associated with dyslipidaemia in high-risk individuals with DM and hypertension in Malawi, hence contributing to the high burden associated with CVDs [34].…”
Section: Discussionsupporting
confidence: 78%
“…In accordance with our observations, findings from a study depicted HDL as the most common lipid abnormality as well as physical activity status was observed to be the crucial determinant of the development of dyslipidemia [ 35 ]. However, in contrast to our outcome, a strong direct correlation of HbA1c was observed between reduced HDL levels and elevated BMI among the subjects of diabetic dyslipidemia [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…A number of risk factors were linked to dyslipidemia among hypertension patients, according to empirical data from earlier literature. These risk variables included sedentary behavior, age, gender, obesity, smoking, diabetes, and a poor diet of fruits and vegetables [ 27 , 28 ]. Although non-healthy food and people’s behaviors are linked to roughly 80% of dyslipidemia [ 29 ], this percentage is still high.…”
Section: Introductionmentioning
confidence: 99%
“…Although non-healthy food and people’s behaviors are linked to roughly 80% of dyslipidemia [ 29 ], this percentage is still high. In addition, Kifle Z et al and Hirigo A et al, respectively, observed high rates of dyslipidemia among Ethiopian hypertensive patients (48.4% and 90.8%) [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation